TRAF3: A novel regulator of mitochondrial physiology and metabolic pathways in B lymphocytes - Jung, Jaeyong; Gokhale, Samantha; Xie, Ping (Frontiers in Oncology, 2023)
Mitochondria, the organelle critical for cell survival and metabolism, are exploited by cancer cells and provide an important therapeutic target in cancers. Mitochondria dynamically undergo fission and fusion to maintain their diverse functions. Proteins controlling mitochondrial fission and fusion have been recognized as essential regulators of mitochondrial functions, mitochondrial quality control, and cell survival. In a recent proteomic study, we identified the key mitochondrial fission factor, MFF, as a new interacting protein of TRAF3, a known tumor suppressor of multiple myeloma and other B cell malignancies. This interaction recruits the majority of cytoplasmic TRAF3 to mitochondria, allowing TRAF3 to regulate mitochondrial morphology, mitochondrial functions, and mitochondria-dependent apoptosis in resting B lymphocytes. Interestingly, recent transcriptomic, metabolic and lipidomic studies have revealed that TRAF3 also vitally regulates multiple metabolic pathways in B cells, including phospholipid metabolism, glucose metabolism, and ribonucleotide metabolism. Thus, TRAF3 emerges as a novel regulator of mitochondrial physiology and metabolic pathways in B lymphocytes and B cell malignancies. Here we review current knowledge in this area and discuss relevant clinical implications.